2020
DOI: 10.4300/jgme-d-20-00657.1
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Resident Work Absence During the COVID-19 Pandemic at a Large Academic Medical Center in New York City

Abstract: Background Montefiore Medical Center (MMC) is a large tertiary care center in the Bronx, New York City, with 245 internal medicine residents. Beginning on February 29, 2020, residents became ill with COVID-19-like illness (CLI), which required absence from work. There was initially a shortage of personal protective equipment and delays in SARS-CoV-2 testing, which gradually improved during March and April 2020. Objective We evaluated the relationship between CLI-related work absence rates of internal medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Taken together, these various complications of COVID-19 may negatively impact the ability of working-age patients to work. As a matter of fact, a large number of studies have reported high rates of sick leave in workers affected by COVID-19 (Alquézar-Arbé et al, 2020;Calvo-Bonacho et al, 2020;Carvalho-Schneider et al, 2021;COVIDSurg Collaborative, 2021;Groenewold et al, 2020;Khorasanee et al, 2021;Merkin et al, 2020;Prezant et al, 2020;Suárez-García et al, 2020). For example, one study using data collected in a UK medical center in March and April 2020 found that 39% of physicians were absent at least once due to sickness, and that absences due to sickness amounted to 1,240 days in the overall sample (Khorasanee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these various complications of COVID-19 may negatively impact the ability of working-age patients to work. As a matter of fact, a large number of studies have reported high rates of sick leave in workers affected by COVID-19 (Alquézar-Arbé et al, 2020;Calvo-Bonacho et al, 2020;Carvalho-Schneider et al, 2021;COVIDSurg Collaborative, 2021;Groenewold et al, 2020;Khorasanee et al, 2021;Merkin et al, 2020;Prezant et al, 2020;Suárez-García et al, 2020). For example, one study using data collected in a UK medical center in March and April 2020 found that 39% of physicians were absent at least once due to sickness, and that absences due to sickness amounted to 1,240 days in the overall sample (Khorasanee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, COVID-19 is not only associated with a wide range of symptoms of a potentially chronic nature but is also a risk factor for poor physical health ( Tanji et al., 2021 ), impaired mental well-being ( Xiong et al., 2020 ), and increased disability ( Pizarro-Pennarolli et al., 2021 ). Taken together, these various complications of COVID-19 may negatively impact the ability of working-age patients to work; in fact, a large number of studies have reported high rates of sick leave in workers affected by COVID-19 ( Alquézar-Arbé et al., 2020 ; Calvo-Bonacho et al., 2020 ; Carvalho-Schneider et al., 2021 ; COVIDSurg Collaborative, 2021 ; Groenewold et al., 2020 ; Khorasanee et al., 2021 ; Merkin et al., 2020 ; Prezant et al., 2020 ; Suárez-García et al., 2020 ). For example, 1 study using data collected in a UK medical centre in March and April 2020 found that 39% of physicians were absent at least once due to sickness and that absences due to sickness amounted to 1240 days in the overall sample ( Khorasanee et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Residents represent an important subgroup with regards to PPE competency, as many were deployed to the front lines during the initial COVID-19 response and may have experienced some of the highest risks for exposure [ 20 ]. At this very institution, a study found that 42% of internal medicine residents deployed during the initial COVID-19 response presented with COVID-19 or COVID-like illness [ 21 ]. This rate is likely comparable to emergency medicine and otolaryngology residents, who held similar roles at the time.…”
Section: Discussionmentioning
confidence: 99%
“…To implement and disseminate these frequent protocol changes we used our 3C approach by coordinating the implementation of these changes through the MCT and communicating these changes to all providers through our various communication methods (see above). As a result of these efforts, resident sick calls returned to pre-COVID levels within weeks despite an ongoing rise in the number of COVID-19 patients hospitalized at our institution ( 8 ).…”
Section: Coordination Communication and Collaborationmentioning
confidence: 99%